Effect of Indoor Temperature Setpoint on HVAC Energy Use and Thermal Comfort in Tropical Classrooms - Hotdian Sinambela; Pramio Garson Sembiring; Haksa Fadilman Sinambela; Mei Derman Hulu; Wilbert Wu (DINAMIS, 2026)
Heating, Ventilation, and Air-Conditioning (HVAC) systems contribute significantly to electricity consumption in tropical educational buildings due to continuous cooling demand. This study evaluates the influence of indoor temperature setpoints on cooling energy consumption and thermal comfort in two university classrooms equipped with split air-conditioning systems in Medan, Indonesia, using EnergyPlus simulations. Six temperature setpoints ranging from 20°C to 25°C were analyzed under identical operational and climatic conditions. Thermal comfort performance was assessed using the Predicted Mean Vote (PMV) method based on ASHRAE Standard 55. To verify the representativeness of the climatic input data, the outdoor dry-bulb temperature obtained from the EPW weather file was compared with observed outdoor temperature data collected on 30 May 2026, resulting in a relative error of 2.26%. The results show that increasing the setpoint temperature reduced annual cooling electricity consumption from 5,515 kWh to 3,607 kWh in Room J20.301 and from 5,284 kWh to 3,581 kWh in Room J20.302, corresponding to energy savings of 34.6% and 32.2%, respectively. However, thermal comfort performance decreased as the setpoint increased. At 25°C, PMV values reached 0.71 and 0.73, exceeding the ASHRAE comfort limit and reducing annual comfort compliance to below 1% in both rooms. The 23°C setpoint provided the most balanced performance, with annual energy consumption of 4,379 kWh and 4,292 kWh while maintaining PMV values within the acceptable comfort range at 0.35 and 0.32. Annual comfort compliance at this condition reached 87.6% and 96.1% for Rooms J20.301 and J20.302, respectively.